Literatura “em série”: uma proposta de letramento literário e estudo do gênero narrativo a partir das séries de TV e das fanfics - Arguejos, Alessandra Oliveira (2019)
This work, developed in the area of languages and literature, presents a proposal of literary literacy that aims to address the problem of the lack of interest of the young person by reading, especially by literary reading. In the methodology, we used the receptive method of reading of the authors Bordini and Aguiar (1988), inspired by the aesthetics of the reception of Jauss (1994), and the basic reading sequence of Rildo Cosson (2009). Applied to an 8th grade elementary school class (32 students), in a public school in the city of Uberlândia, the project was carried out in the form of workshops lasting seven months (to February to September of 2018) and being divided into three parts (Part I, Part II and " The spin of Knowledge in Literature "). We started the activities with the receptive method, attending the expectations horizons of the students, using for that TV series and fanfics. Next, we proposed the expansion of the expectation horizons of these adolescents with the reading of a literary work, which thematically dialogues with the previously read genres. In reading the book, we follow the steps of the basic reading sequence: motivation, introduction, reading and interpretation. During this reading, we seek to explore the three forces of literature (BARTHES, 1989), incorporating into the process various forms of artistic manifestations such as: music, dance, poetry, cinema and art. We turn to virtual learning environments to create more interaction with students and with the involvement of technology, encompassing to the proposal the multiliteracy and digital literacy. The digital platform was very useful, facilitating the registration of workshops, evaluations and self-evaluations of students about the process. We idealized the creation of a differentiated, seductive project that would provide to the students forms of collaborative learning and the acquisition of meaningful and interesting knowledge for them. We hypothesized that a diversified work with the literature at the classroom and the use of resources such as TV series and fanfics can offer for these young people the broadening of their expectations horizons, thus creating a greater interest in literary reading. We seek to report the results, detailing the activities performed by adolescents in this process, as well as their opinions and evaluations about it.